The inescapable self : an introduction to Western philosophy since Descartes - Chappell, T. D. J. (Timothy D. J.) (London : Weidenfeld & Nicolson, 2005)
"Walking in the footsteps of Plato and Descartes, Timothy Chappell recognizes that 'the fortress of my certainty about my own existence becomes the prison of my uncertainty about the existence of a world beyond me'. Using this insight as a springboard, Chappell launches into an exploration of a series of intellectual dilemmas that are the very stuff of philosophy: how can we know things outside ourselves? What basis is there for altruistic behaviour? Can we bridge the gap between mind and world? Do we have free will?" --Book Jacket
Includes bibliographical references (p. [319]-328) and index
Keywords: Philosophy; Skepticism; Self (Philosophy)